Astrocytes Resist HIV-1 Fusion but Engulf Infected Macrophage Material - Rebecca A. Russell; Jakub Chojnacki; Daniel M. Jones; Errin Johnson; Thao Do; Christian Eggeling; Sergi Padilla-Parra; Quentin J. Sattentau (Cell Reports, 2017)
HIV-1 disseminates to diverse tissues and establishes long-lived viral reservoirs. These reservoirs include the CNS, in which macrophage-lineage cells, and as suggested by many studies, astrocytes, may be infected. Here, we have investigated astrocyte infection by HIV-1. We confirm that astrocytes trap and internalize HIV-1 particles for subsequent release but find no evidence that these particles infect the cell. Astrocyte infection was not observed by cell-free or cell-to-cell routes using diverse approaches, including luciferase and GFP reporter viruses, fixed and live-cell fusion assays, multispectral flow cytometry, and super-resolution imaging. By contrast, we observed intimate interactions between HIV-1-infected macrophages and astrocytes leading to signals that might be mistaken for astrocyte infection using less stringent approaches. These results have implications for HIV-1 infection of the CNS, viral reservoir formation, and antiretroviral therapy.